The intriguing role of collagen on the rheology of cancer cell spheroids. (August 2022) - Tsvirkun, Daria; Revilloud, Jean; Giannetti, Arianna; Verdier, Claude
Abstract: Spheroids are multicellular systems with an interesting rheology giving rise to elasto-visco-plastic properties. They are good tumor models, but the role of the extracellular matrix (ECM) is not fully understood. ECM is an important link between cells and may have a significant impact on tissue organization. Here we determine viscoelastic properties of spheroids including different collagen I amounts using AFM and predict new frequency–dependent properties leading to soft glassy rheology behavior. A unified model – similar to single cell behavior – is proposed and discussed, while complementary confocal experiments reveal the microstructure of spheroids, with collagen I fibers serving as a skeleton for cells, thus reinforcing the spheroid viscoelastic behavior. Graphical abstract: